Calculation of adjoint-weighted reactor kinetics parameters in OpenMC. (June 2019) - Peng, Xingjie; Liang, Jingang; Forget, Benoit; Smith, Kord
Highlights: The capability of calculating adjoint-weighted kinetics parameters has been implemented in OpenMC. IFP method and CLUTCH method have been used in OpenMC to perform adjoint weighting. The results of OpenMC have been benchmarked by comparison to MCNP5 and experimental data. Abstract: Knowledge of adjoint-weighted kinetics parameters plays an importance role in analyzing the reactor safety and in describing the transient behavior of nuclear reactors during normal operation or accidents. In this work, the capability of calculating adjoint-weighted kinetic parameters, including the effective neutron generation time and the effective delayed neutron fraction was implemented in OpenMC code based on three different methods of interpreting the physical meaning of the adjoint weighting, namely, the next fission probability (NFP) method, the iterated fission probability (IFP) method and the Contribution-Linked eigenvalue sensitivity/Uncertainty estimation via Tracklength importance CHaracterization (CLUTCH) method. The results of the implementation were benchmarked by comparison to MCNP5 calculations and experimental data in several critical configurations.